Value Narratives in Sexuality Education: Teachers’ Preparedness or Retreat? - Bytautas, Marius; Daukilas, Sigitas (Pedagogika, 2023)
The paper analyses the value narratives on youth sex education presented to the public by influencers and parents of school-age children. The research questions are: what is the content of the value narratives in the field of sexuality presented to the public by influencers and parents of school-age children? what is the motivational environment for teachers delivering sex education? what are the possible principles of communication between teachers, organisations involved in sex education, and parents? The empirical research data were collected using a mixed methods strategy. The methodological and value differences between the institutions providing sex education in Lithuania were found to be insignificant, nevertheless, there are significant differences in the value narratives between the concepts of ‘sexuality education’ and ‘sex education’ in the public sphere. Parents of school-age children are exposed to fragmented, value-indoctrinated sex education content presented by influencers, leading to social tensions in school communities regarding children’s sex education. The analysis of the narratives of influencers and parents on the topic of sex education shows that the constructive participation of interested groups (educators, parents, social organisations) in the policy of sex education is impossible without the principles of critical analysis, attention to conflicts, and social dialogue.